Are β‐H Eliminations or Alkene Insertions Feasible Elementary Steps in Catalytic Cycles Involving Gold(I) Alkyl Species or Gold(I) Hydrides?. Issue 12 (10th February 2013) - Klatt, Günter; Xu, Rong; Pernpointner, Markus; Molinari, Lise; Quang Hung, Tran; Rominger, Frank; Hashmi, A. Stephen K.; Köppel, Horst
Abstract The β‐H‐elimination in the (iPr)AuEt complex and its microscopic reverse, the insertion of ethene into (iPr)AuH, were investigated in a combined experimental and computational study. Our DFT‐D3 calculations predict free‐energy barriers of 49.7 and 36.4 kcal mol−1 for the elimination and insertion process, respectively, which permit an estimation of the rate constants for these reactions according to classical transition‐state theory. The elimination/insertion pathway is found to involve a high‐energy ethene hydride species and is not significantly affected by continuum solvent effects. The high barriers found in the theoretical study were then confirmed experimentally by measuring decomposition temperatures for several different (iPr)AuI–alkyl complexes which, with a slow decomposition at 180 °C, are significantly higher than those of other transition‐metal alkyl complexes. In addition, at the same temperature, the decomposition of (iPr)AuPh and (iPr)AuMe, both of which cannot undergo β‐H‐elimination, indicates that the pathway for the observed decomposition at 180 °C is not a β‐H‐elimination. According to the calculations, the latter should not occur at temperatures below 200 °C. The microscopic reverse of the β‐H‐elimination, the insertion of ethene into the (iPr)AuH could neither be observed at pressures up to 8 bar at RT nor at 1 bar at 80 °C. The same is true for the strain‐activated norbornene.